(untitled) (Third Sector Social Economic Review, 2025)
In this study, the relationships between the variables of emotional commitment, organizational trust and organizational citizenship behavior were examined on the basis of employees working in medium-sized enterprises in Kahramankazan district of Ankara. According to the analysis results, emotional commitment and trust scores of individuals between the ages of 25-35 were lower, while those aged 46 and over had higher trust in the manager and the institution. Married individuals had higher emotional commitment and organizational trust scores than single individuals. According to the level of education, emotional commitment scores of associate degree graduates were higher than postgraduate graduates, while high school graduates had lower scores in the sub-dimensions of trust in the manager and the institution. Those whose income was less than their expenses had lower emotional commitment and trust scores, while those whose income was equal to their expenses had higher formal role behavior and organizational citizenship behavior scores. As the duration of employment increased, emotional commitment and trust scores increased. Individuals with job satisfaction have higher emotional commitment, organizational trust and organizational citizenship behavior scores. A positive medium relationship was found between emotional commitment and organizational trust, a weak relationship between emotional commitment and organizational citizenship behavior, and a moderate relationship was found between organizational trust and organizational citizenship behavior. In addition, organizational trust has a full mediating role in the effect between emotional commitment and organizational citizenship behavior.